New Record of Edible Chicken of the Wood Mushroom, Laetiporus versisporus (Lloyd) Imazeki (Fomitopsidaceae, Polyporales) from Sabah (Northern Borneo), Malaysia - Ily Azzedine Alaia Mh Subari; Jaya Seelan Sathiya Seelan; Tan, Yee Shin (UNIMAS, 2023)
The genus Laetiporus has been previously reported from Mesilau in Sabah, Northern Borneo in 1964. To date, no further documentation of the Laetiporus genus has been reported in Sabah, Malaysia. This study provides an overview of recent literature on taxonomic updates, distribution and sequence data of Laetiporus in Malaysia. During the period March – June 2020, two Laetiporus specimens were collected in Maliau Basin Conservation Area and Sipitang. These two specimens were identified as L. versisporus based on morphological characteristics and molecular methods. Interestingly, no sequence data for this particular species have been documented for Malaysian Borneo. This study represents the initial documentation of L. versisporus in Sabah (Northern Borneo) that have potential applications in medicine and food industry and provide insights into its phylogenetic relationship within the genus Laetiporus.